ISOLASI BAKTERIOFAG Salmonella spp. dari BIOFILM pada SISTEM AIR MINUM ISI ULANG - Rahayu Damayanti; Siti Nur Jannah; w wijanarka; Sri Hartin Rahaju (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
The public demands for the refill drinking water increases causing the development of refill drinking water industries. However, the problems occurred is no standard method to process drinking water with sterile and lack of government oversight. These cases give rise to sanitation which is the formation of bacteria pathogen forming biofilms in refill drinking water system. One of the bacteria pathogens is Salmonella. Salmonella in refill drinking water can cause diarrhea, because it can produce cytotoxin and enterotoxin. Bacteriophages are viruses that infect bacteria. This study aims to find natural isolates of bacteriophage from biofilm samples to infect Salmonella spp. in refill drinking water system. The isolates obtained is then characterized by biochemical test including Gram stain, a test Kligler Iron Agar (KIA) and api assay 20 E. The positive Salmonella spp. isolates are in the second dilution refill drinking water depot. The isolation of bacteriophage from biofilm is conducted with bacteriophages amplification and bacteriophage filtrate. The Infection test is performed by using Salmonella enterica, Salmonella 7A1 from Teluk Ambon and Salmonella spp. from refill drinking water depot. Platting is performed on serial dilutions of 10-2 to 10-10phage dilution. Positive result is characterized by the formation of plaque which is in source water samples, water product and drinking water depot. The number of plaques formed is calculated by Plaque Forming Units (PFU/mL) to determine quantification or calculation phages.